KARAKTERISASI MIDORIKO SEBAGAI TOKOH PUBERTAS DALAM NOVEL CHICHI TO RAN KARYA KAWAKAMI MIEKO - Arum Martian Puspasari; Fenny Febrianty (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2022)
This research aims to describe the form of the character of Midoriko who is experiencing puberty in the novel Chichi to Ran by Kawakami Mieko in terms of Albertine Minderop's characterization theory, namely direct and indirect methods. The research method used in this research is descriptive analysis with a structural approach. The main data source of this research is the novel Chichi to Ran by Kawakami Mieko. Based on the results of the analysis, it is known that the characteristics of Midoriko's character in the novel Chichi to Ran are a woman who is just a teenager, going through puberty which makes her character sensitive and unstable, making her question her biological function. Keywords: puberty, characterization, childs character, japanese literature, novel